Design and Fabrication on Model on Solar Train - Jeeva Bharathi, S.; Kumar Singh, Karan; Kumar, Krishna; Sahid Akhtar, Md.; Kumar Pandey, Nitesh (International Journal of Psychosocial Rehabilitation, 2019)
As we all know that technology is double edged weapon which can turn any satution either into a boon or bane. In recent years we are much familiar with the word “global warming”.Increase in the average temperatureof the earth’s near suraface air and the oceans. In this paper we are going to explain you about the largest financed domestic project by United Nations for the year 2014. The best way to control this is by efficient use of renewable energy and this is our stream of interest to use solar energy in driving railways which arises the concept of “ Solar Train”. Implementing solar energy usage in addition coserves ergy source to an extent solar pannels fitted on roof of the train used to convert solar to electrical energy and using some technical methods to utilize that energy. The purpose of this research is to examine new solar technologies, in order to gain insight and full understanding regarding alternative energy. Both research ideas and implemented technology is elaborated on. Moreover, ethical issues surrounding this technology are presented and problems preventing its solution are uncovered. In conclusion, the efficiency of solar is challenged and basic statistics assist in this determination.